Business models for Industry 4.0 : concepts and challenges in SME organizations - Grabowska, Sandra; Saniuk, Sebastian (Routledge studies in innovation, organizations and technology, 2023)
"Utilising industry 4.0 technologies is essential to meet consumer expectations of personalised products and services but not without obstacles and challenges. This book provides comprehensive knowledge on the operating conditions and challenges of small and medium-sized enterprises operating in the era of industry 4.0 and proposes a business model 4.0 concept. The authors provide insights on the general conditions for the development of economy 4.0 and society 5.0, the expectations of modern consumers in product personalization, customization, servitization and the SME sector's requirements. In addition, the book offers a business model of cooperation between enterprises and the concept of rapid network prototyping methodology for the implementation of personalized products. It proposes the creation of e-business platforms that will allow for better integration of the customer with the manufacturer and the possibility of greater involvement in product configurations. The empirical research offered in this book will provide valuable insights for scholars and upper-level students across business disciplines, including strategic management, entrepreneurship, technology and innovation management"--